United Arab Emirates : 2008 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The United Arab Emirates' (UAE) macroeconomic performance during 2007-08 was strong, with growth especially in the construction and services sectors. Annual average inflation accelerated, driven by domestic demand pressures. Executive Directors have commended the authorities for their outward-oriented development strategy and the impressive performance of the economy in recent years. Directors have also emphasized the importance of safeguarding the soundness and functioning of the financial sector, while facilitating a smooth and orderly deceleration in credit growth from an unsustainable pace.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet